Patient Portal Registrations at a Swiss Tertiary Referral Hospital Over the Course of the COVID-19 Pandemic: Retrospective Data Analysis - Anita D Linke; Amanda Franklin-Ryan; Angela Horn; Patrick E Beeler; Balthasar L Hug (Journal of Medical Internet Research)
Abstract BackgroundTo enhance patient empowerment, the Cantonal Hospital of Lucerne launched a patient portal (MyChart) in December 2019, granting patients access to their medical records, diagnoses, and laboratory results. Months later, the first COVID-19 case was reported in Switzerland, with the pandemic dramatically affecting health care services. ObjectiveThis analysis aims to investigate how the pattern of patient portal registrations evolved during the pandemic, with reference to the spread of COVID-19, as well as local and federal policies. MethodsThis retrospective observational study analyzed the distribution of patient portal registrations after its introduction at the study site from December 1, 2019, until July 31, 2022. The descriptive analysis included the 7-day mean of registrations, plotted alongside the number of administered COVID-19 tests and COVID-19 vaccinations. This was analyzed concerning predefined time periods and stratified by age and gender. Additionally, an interrupted time series analysis was conducted for the different time periods. ResultsA total of 126,519 patients registered on the patient portal during the study period, with a slightly higher proportion of female patients (n=66,118, 52.3%) and 11.3% (n=14,259) being 65 years of age or older. The daily registration rate differed substantially over the course of the COVID-19 pandemic, whereby four peaks with >200 registrations per day were identified. The first and third peaks coincide with high COVID-19 testing rates in autumn 2020 and 2021, whereas the second and fourth peaks coincide with the release of the vaccine in spring 2021 and the booster at the end of 2021. These patterns are also reflected in the interrupted time-series analysis: for every transition from one period to the next, the immediate effect of the intervention (level change) is statistically significant with P ConclusionsThe COVID-19 pandemic, with its disease dynamics, including testing and vaccinations, seems to have influenced the number of patient portal registrations. In addition, it appears that patients aged 65 years or older predominantly registered for COVID-19 vaccines.